Pelaksanaan Penilaian Status Gizi Siswa Sekolah Dasar Dalam Upaya Penyusunan Intervensi Gizi Di Sekolah Dasar Di Jakarta Selatan - Titus Priyo Harjatmo (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The prevalence of overweight and obesity among children is rising. Childhood obesity rates continue to climb in various countries, including Indonesia. Data from the 2018 Basic Health Research (*Riset Kesehatan Dasar*) indicate that the prevalence of obesity among children aged 5–12 remains significant at 18.8%, comprising 10.8% who are overweight and 8.8% who are obese. Childhood obesity can lead to various health issues, such as diabetes, hypertension, and high cholesterol. The accumulation of body fat triggers numerous health problems—including diabetes, lipid disorders, cardiovascular disease, and cancer—that can diminish an individual's quality of life. Regarding its impact on the cardiovascular system, obesity affects the heart's function in circulating blood throughout the body via blood vessels. The arteries transporting blood from the heart are not merely passive tubes but a network of vessels actively involved in regulating blood flow. Excess weight in children is a particular concern because it carries the potential to lead to health issues typically associated with adults, such as diabetes, hypertension, and high cholesterol. Identifying nutritional status is a crucial step in developing appropriate nutritional interventions for school students. This activity was conducted at an elementary school in Kebayoran Baru, South Jakarta, in May 2026.